Identification of Theaflavin-3,3'-Digallate as a Novel Zika Virus Protease Inhibitor - Xiangling Cui; Rui Zhou; Chenchao Huang; Chenchao Huang; Rongyu Zhang; Rongyu Zhang; Jing Wang; Yongxin Zhang; Jiwei Ding; Jiwei Ding; Xiaoyu Li; Jinming Zhou; et al. (Frontiers Media S.A., 2020)
Mounting evidence indicates that Zika virus (ZIKV) is closely related to neurological disorders such as microcephaly and Guillain-Barré syndrome. There are currently no effective vaccines and FDA-approved inhibitors against ZIKV infection. The flaviviral heterodimeric serine protease NS2B-NS3 plays an essential role in ZIKV maturation and replication, thus becoming a promising target in anti-ZIKV therapy. Herein, we developed a fluorescence-based screening assay to search for inhibitors targeting the ZIKV NS2B-NS3 protease (ZIKVpro), and identified theaflavin-3,3'-digallate (ZP10), a natural active compound derived from black tea, as a potent ZIKV protease inhibitor in vitro (IC50 = 2.3 μM). ZP10 exhibited dose-dependent inhibitory effect on ZIKV replication (EC50 = 7.65 μM). Western blot analysis suggested that ZP10 inhibited the cleavage processing of viral polyprotein precursor in cells either infected with ZIKV or expressing minimal self-cleaving proteinase NS2B-3 protease, resulting in inhibition of virus growth. Moreover, ZP10 was showed to directly bind to ZIKVpro, and a docking model further revealed that ZP10 interacted with several critical residues at the proteolytic cavity of the ZIKVpro. This study highlights that ZP10 has anti-ZIKV potency through ZIKVpro inhibition, which indicates its potential application in anti-ZIKV therapy.